Agribusiness Adaptation and Risk Management Strategy Based on Rice Prediction to Strengthen Sustainable Food Governance in Jemberaddy Prediction Interpretation for Food Governance Planning in Jember Regency - Hotima, Siti Husnul; Prabawati, Achadyah; Rohim, Rohim (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2026)
Food security is a strategic issue that has become a priority for sustainable development. Jember Regency, as one of the rice production centres in East Java, faces various challenges in realising sustainable food security. This research aims to explore and analyse adaptation strategies and risk management in paddy agribusiness by employing a paddy prediction interpretation approach as the basis for food governance planning. The research utilises a descriptive-exploratory qualitative approach with an interpretivist paradigm. Data were collected through in-depth interviews with various informants, including farmers, farmer group administrators, agribusiness practitioners, officials from the Department of Agriculture, agricultural extension workers, and academics. Secondary data were obtained from the Central Bureau of Statistics and the Department of Agriculture of Jember Regency. Data analysis employed a thematic analysis approach following Miles and Huberman. The research findings indicate that Jember Regency maintains a consistent surplus in paddy production, averaging approximately 30,000 tonnes per annum. Paddy agribusiness actors face production risks, price risks, institutional risks, financial risks, and personal risks. The adaptation strategies implemented encompass technical, economic, social, and institutional strategies. The utilisation of paddy prediction interpretation in planning remains suboptimal, with an information access gap between policy and operational levels. This research recommends the development of an integrated food security information system, strengthening multi-stakeholder coordination, increasing investment in agricultural infrastructure, and developing social protection schemes to reinforce sustainable food security in Jember Regency.